Survei Pembinaan Klub Sepakbola PS. AD Kota Semarang (Universitas Negeri Semarang, 2021)
One effort to meet the target and get the desired achievement in sports achievement is to build a good coaching pattern. The purpose of the study was to determine the coaching achievements of football clubs PS AD in the City of Semarang. This research is a type of qualitative research. The research instruments used were observation, interviews, and documentation. Data authenticity check that utilizing to utilize triangulation. Analizing is data utilizes data reduction, data display, and data conclusion drawing / verification. The results of research conducted show that, 1) Coach who coaches PS soccer clubs. AD numbered 3 people, namely the head coach, assistant coach, and goalkeeping coach and all already have an official training license with the highest license C AFC license, 2), the organizational structure at the PS soccer club. The Army has been well structured and with a clear SOP with Dandim as the Chairman of the Regional Military Command as well as the General Chair 3) Funding obtained from the club PS. AD is sourced from military unit funds and also some cooperates with sponsors, 4) PS football club training program. The Army has been well structured because it has a training program that covers aspects of physical training, mental training, tactics training and technical skills, and 5) Facilities and infrastructure owned by the soccer club PS AD is in accordance with the standards. The conclusion in this study is the coaching of football clubs PS. AD in the city of Semarang has been going well.